Mineral Trioxide Aggregate Versus Calcium Hydroxide in Direct Pulp Capping: A Review of Literature - Alrabiah, Abdullah Mohammed (International Journal of Innovative Research in Medical Science, 2020)
Direct pulp-capping is a treatment for exposed vital pulp involving the placement of a dental material over the exposed area. This facilitates both the formation of protective barrier and the maintenance of vital pulp. Direct pulp capping (DPC) has been used as an alternative approach to the maintenance of vital pulp. So, many tooth extractions and root canal treatments could have been avoided through the conservative approach of direct pulp capping. For this purpose, different kinds of materials used such as Zinc Oxide Eugenol, Glass Ionomer (GI), Resin Modified Glass Ionomer (RMGI), Adhesive systems, Calcium Hydroxide (CH), Mineral Trioxide Aggregate (MTA) and Bio dentine. MTA performed more effective than conventional Calcium Hydroxide clinically as a direct pulp capping material. MTA showed higher success rate than dycal. MTA is easier to use clinically as a direct pulp capping material. MTA also provided better long-term results and more effective than Calcium Hydroxide in maintaining long-term vitality. MAT is significantly less toxic, less pulpal inflammations. Furthermore, MTA is more predictable than dycal in formation of dentin barrier and superior than Calcium Hydroxide in dentinogenetic process in human pulp. MTA is more effective and superior comparing the Calcium Hydroxide as a direct pulp capping material, demonstrating higher success rate with favorable outcomes in maintaining long term tooth vitality and easier to use in pulp capping. Finally, MTA is more cost-effective than CH for DPC despite higher initial treatment costs because expensive retreatments were avoided.